Aporte por regulación, canon por espectro Radioeléctrico y tasa por explotación comercial: Aspectos tributarios de las telecomunicaciones - Soto Carrillo, Gerardo (2016)
The Peruvian government has stablished mandatory payments that telecom companies have to make: the regulatory contribution, the tariff for radio spectrum and the fee for commercial exploitation.In this article, the authors examine what tax nature and what validity basis those impositions have.